Honky Tonk Hairdos: Winifred Atwell and the Professionalization of Black Hairdressing in Britain. (2nd November 2018) - Smith, Kim
Abstract : This article will examine the circumstances surrounding the professionalization of black hairdressing in Britain, which was relatively unknown before the 1950s. Prior to this Britain's African and Caribbean diaspora was scattered throughout the country in small communities, warranting little attention from white hairdressers who seldom had occasion or the expertise to cut or dress black hair. All this was to change after the Second World War, with increased immigration, and the arrival of one person in particular, whose gifted musical talents endeared her to the nation. This article focuses on the role of Winifred Atwell (1914–1983) who, as a chart-topping entertainer in the British public spotlight, recognized that her appearance required high maintenance in dress, make-up and hair. As a canny entrepreneur, Atwell identified a dearth in professional black hairdressing and to facilitate her personal hair-grooming regime, opened her own salon in South London where she had other business connections. It was also an area which experienced a high volume of Caribbean settlement. Atwell's needs and the acceleration of post-war migration were catalysts in the move from amateur domestic hairdressing to public black salons. The discussion also considers the challenges that black women faced in terms of their hair and beauty and how they sought to overcome this through visual integration with Westernized beauty ideals. It will attempt to demonstrate that Atwell became a role model through her entrepreneurship, inspiring the social aspirations of ordinary black women to establish their own businesses, professionalize their skills through training and education, and seek affiliation with white hairdressing organizations as part of a more incorporated credentialism, despite evergrowing racial tensions.